2004
DOI: 10.1016/j.febslet.2004.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the stalk subunit Vma5p of the yeast V‐ATPase in solution

Abstract: Vma5p (subunit C) of the yeast V-ATPase was produced in Escherichia coli and purified to homogeneity. Analysis of secondary structure by circular dichroism spectroscopy showed that Vma5p comprises 64% a-helix and 17% bsheet content. The molecular mass of this subunit, determined by gel filtration analysis and small angle X-ray scattering (SAXS), was approximately 51 % 4 kDa, indicating a high hydration level of the protein in solution. The radius of gyration and the maximum size of Vma5p were determined to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 52 publications
4
53
0
Order By: Relevance
“…An intriguing result was the formation of a stable and ATPase active hybrid complex composed of Vma5p and V 1 from M. sexta, lacking endogenous subunit C. It has been demonstrated that the addition of recombinant subunit C to the V 1 (-C) complex significantly increased ATPase activity [13], supporting its functional role in regulation of ATPase activity [15,16]. Here, we report for the first time the property of nucleotide binding of subunit C, independently observed by photoaffinity labeling and fluorescence correlation spectroscopy (FCS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intriguing result was the formation of a stable and ATPase active hybrid complex composed of Vma5p and V 1 from M. sexta, lacking endogenous subunit C. It has been demonstrated that the addition of recombinant subunit C to the V 1 (-C) complex significantly increased ATPase activity [13], supporting its functional role in regulation of ATPase activity [15,16]. Here, we report for the first time the property of nucleotide binding of subunit C, independently observed by photoaffinity labeling and fluorescence correlation spectroscopy (FCS).…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy studies of the disassembled V 1 complex from tobacco hornworm Manduca sexta have shown that subunit C dissociates from the V 1 subcomplex [11], although it is essential for the reassembly of the functional V 1 V 0 [9,12]. Previously, the structure of the C subunit (Vma5p) from the yeast V 1 V 0 ATPase has been studied by small angle X-ray scattering, revealing that the hydrated Vma5p has an elongated bootshaped structure with a maximum size of 12.5 nm [13]. A recent 1.75 Å map from X-ray diffraction studies of Vma5p [14] confirms this feature and shows that this subunit consists of three distinct domains.…”
Section: Introductionmentioning
confidence: 99%
“…A Profilin-like Sequence in the V-ATPase Subunits B and CLow resolution x-ray scattering recently revealed an elongated boot-shaped form of the yeast subunit C (34). However, up to now no high resolution structural analysis exists which is a necessary precondition for the prediction of actin binding domains.…”
Section: Fig 2 Overlay Slot-blots Reveal Binding Of Subunit C To Bomentioning
confidence: 99%
“…SAXS, for example, has been used to describe the structure and morphology of the C subunit and its role in V-ATPase regulation (Svergun et al, 1998;Armbruster et al, 2004) (Figure 3).…”
Section: The C Subunitmentioning
confidence: 99%